Crafting a vision & mission statement for the competition commission of India - Sharma, Sunil, 1960-; Varkkey, Biju (London : Indian Institute of Management, Ahmedabad, 2014)
The case describes the process of formulating Vision and Mission (hereafter V&M) statement for a competition regulator. It provides chronology of setting up the commission and also describes the focus of the act, some recent penalties imposed on firms, and the need to formulate the V&M statement. The process included the identification of stakeholders, methodology for seeking their views, and brief descriptions of the views expressed by the stakeholders. Participants are challenged to develop a V&M statement for the commission.
Originally published in Sharma, S., & Varkkey, B. (2014). Crafting a vision & mission statement for the Competition Commission of India. BP0392. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mission statements -- India